2014
DOI: 10.3126/ajms.v6i1.10181
|View full text |Cite
|
Sign up to set email alerts
|

A simple method to detect plant based inhibitors of glycation induced protein cross-linking

Abstract: Background: Glycation induced cross-linking of proteins are associated with chronic diabetic complications. Inhibition of protein glycation is one of the therapeutic approaches to prevent the progression of diabetic complications. Objective: Objective of this study was to establish a simple method to identify medicinal plants which can inhibit glycation induced protein cross-linking. Methods: Lysozyme was incubated at 37°C up to 4 weeks with different concentrations of glucose, fructose and ribose in sodium ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 17 publications
2
9
0
Order By: Relevance
“…It indicated that BSA proteins formed higher molecular weight new proteins. These protein products were cross‐linked protein induced by glycation under fructose (Perera & Ranasinghe, ). Figure a shows kaempferol had antiglycation activity, which was in a dose‐dependent manner.…”
Section: Resultsmentioning
confidence: 97%
“…It indicated that BSA proteins formed higher molecular weight new proteins. These protein products were cross‐linked protein induced by glycation under fructose (Perera & Ranasinghe, ). Figure a shows kaempferol had antiglycation activity, which was in a dose‐dependent manner.…”
Section: Resultsmentioning
confidence: 97%
“…Studies conducted to investigate protein glycation inhibitors have used expensive specialized equipments [ 9 ]. Previously we have optimized a simple SDS-PAGE method using lysozyme to detect the inhibitory effects of plant extracts on glycation induced lysozyme cross-linking [ 10 ]. Even though the glycation induced protein cross-linking inhibition by pure compounds has been studied using the SDS-PAGE method before [ 12 ], no reports were available for its application for crude plant extracts.…”
Section: Discussionmentioning
confidence: 99%
“…Being a protein with a pI of 11.35 and having 6 Lysine residues and 11 Arginine residues which are the targets of glycation, lysozyme serves as a good candidate for glycation induced protein modifications. Lysozyme showed extensive cross-linking under the conditions that increase the protein glycation such as increase in the sugar concentration, incubation period and the reactivity of the sugar [ 10 ]. With SDS-PAGE, products of glycation induced cross-linking appeared as high molecular weight bands [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations